Caridina malanda, a new species of freshwater shrimp (Crustacea: Decapoda: Atyidae) from the Wet Tropics World Heritage area, north–eastern Queensland, Australia - Choy, Satish; Page, Timothy J.; de Mazancourt, Valentin; Mos, Benjamin (Zootaxa, 2019)
Integrated molecular and morphological studies of newly collected and curated specimens of the genus Caridina from the Atherton Tablelands, Wet Tropics World Heritage Area in north–eastern Queensland, Australia indicated the presence of an undescribed species belonging to the Caridina zebra Short 1993 complex. This species is somewhat intermediate, although distinct on the basis of molecular data and morphology, from two known sympatric species, Caridina zebra and C. confusa Choy & Marshall 1997, and an allopatric species, C. spinula Choy & Marshall 1997, from the Cape York Peninsula, about 500 km north. It is described here as a new species, C. malanda sp. nov., and compared with similar congeners. A key for the identification of the species, as well as notes on its distribution, ecology, and conservation, are provided.